Síntese e Caracterização de Biofilme à base de quitosana e glicerol para aplicação em embalagens de alimentos - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Polymers synthesized from renewable sources are called biopolymers, and represent an alternative to petroleum-derived plastics that have a negative impact on the environment. The need for large-scale production of packaging for daily use in the market has made polymers a prominent role in virtually all production segments. Currently there is a great interest in the research and development of materials for biodegradable food packaging in order to reduce the accumulation of plastic waste. Chitosan is a copolymer of natural origin, biodegradable, derived from the process of deacetylation of chitin, and has characteristics that allow a wide versatility of application, and can be used in the production of biofilms. To supply the characteristics of synthetic polymers, such as flexibility, strength and permeability it is necessary to add a plasticizing agent in the formulation to have better interaction of components and ensure a quality similar to those of synthetic polymers. One of the objectives of plasticizing agents is to confer flexibility, and in some cases, to improve the processability of the material. Glycerol is a by-product of the biodiesel industry, considered a low-cost plasticizing agent that has favorable characteristics when in contact with polymers of natural origin. Throughout the above, the present work aimed to produce films based on chitosan and glycerol at different concentrations by casting method, characterize the biofilms formulated with the aid of thickness, vapor permeability (PVA) analyses, mechanical tensile assay, intumesation index, X-ray diffraction (XRD) and thermogravimetric analysis (TGA) to verify a possible use in food packaging. In addition, the results obtained in the analyses were compared with a commercial polymer, PVC. The results showed that glycerol favored the formation of less thick films and pure chitosan film obtained the lowest PVA value. The degree of intumesination showed the total dissolution of pure chitosan film in less than an hour and those with glycerol absorbed 761% of mass in 48h of test. Both films had similar thermal behavior. Film with pure chitosan showed a rigid mechanical behavior while the addition of glycerol improved flexibility.
Keywords: Quitosana; Biofilme; Glicerol; Biodegradável.; Chitosan; Biofilm; Glycero; Biodegradable; CNPQ::ENGENHARIAS